Optimization of Job Descriptions and Job Specifications on Employee Performance in Bandung State Administrative Court - Asep Ahmad Sudrajat (Green Publisher Indonesia, 2021)
The purpose of this study is to see the effect of job descriptions and job specifications either partially or simultaneously on employee performance in solving cases and to explain their optimization in order to achieve timely settlement of cases. This research is a combined research between descriptive and causal designs. The variable shows the research data is valid and reliable. The total population is 47 people. The sample was used as much as 46 survey respondents questionnaire and respondents 1 interview. The independent variables of this study are job descriptions (X1) and job specifications (X2) which are covered by employee performance in case resolution (Y). Measurement using ordinal measurement scale variables with a Likert attitude scale. Data analysis used descriptive analysis and inferential analysis using SPSS 25.0 application. From the results of research and discussion, it can be concluded that the job descriptions variable does not have a partial effect on Employee Performance in Case Resolution at PTUN Bandung. Job specifications variable gives a partially significant influence on Employee Performance in Case Resolution at PTUN Bandung. Job descriptions and job specifications variables have a significant effect simultaneously (simultaneously) on Employee Performance in Case Resolution at PTUN Bandung. The implementation of job descriptions and job specifications can optimize employee performance so that it can realize case resolution at PTUN Bandung as mandated by SEMA Number 2 of 2014.